1999
DOI: 10.1002/(sici)1098-2795(199910)54:2<103::aid-mrd1>3.3.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal apoptosis inhibitory protein (NAIP) may enhance the survival of granulosa cells thus indirectly affecting oocyte survival

Abstract: In mammals, the postnatal loss of more than 99% of female germ cells is due mainly to the process of ovarian follicular atresia. Atresia is known to be mediated by apoptotic granulosa cell-death. Here we show the involvement of neuronal apoptosis inhibitory protein (NAIP) in ovarian folliculogenesis in which it prevents granulosa cell-death. NAIP has been isolated in association with a neurodegenerative disorder, spinal muscular atrophy (SMA), in which it has been shown to suppress mammalian cell-death induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…LTR promoters may be particularly responsive to upregulation by cellular stresses since it has been shown that activation of human and mouse ERV LTRs can occur following stresses such as viral infection [54][55][56] and UV irradiation [57,58]. Various IAPs are expressed in human [59,60], mouse [61], and rat [62,63] germ cells or their progenitors, and it has been reported that Naip expression plays a role in mouse oocyte viability [61]. Although nothing is known about a potential NAIP stress response in the germ line, it has been demonstrated that NAIP mRNA and protein is upregulated in neurons following ischemic stress [64].…”
Section: Discussionmentioning
confidence: 99%
“…LTR promoters may be particularly responsive to upregulation by cellular stresses since it has been shown that activation of human and mouse ERV LTRs can occur following stresses such as viral infection [54][55][56] and UV irradiation [57,58]. Various IAPs are expressed in human [59,60], mouse [61], and rat [62,63] germ cells or their progenitors, and it has been reported that Naip expression plays a role in mouse oocyte viability [61]. Although nothing is known about a potential NAIP stress response in the germ line, it has been demonstrated that NAIP mRNA and protein is upregulated in neurons following ischemic stress [64].…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal apoptosis inhibitory protein (NAIP) and survivin have been detected in granulosa cells from primary follicles up to the preovulatory stage. Moreover, like XIAP, expression of these IAPs is stimulated by gonadotrophins (Matsumoto et al 1999, Kumazawa et al 2004. A relationship between low Naip1 (Naip) mRNA expression levels in granulosa cells and reduced ovulated oocyte quality has been observed, indicating that NAIP may act indirectly to promote oocyte viability in the mouse ovary (Matsumoto et al 1999).…”
Section: Other Iaps In the Ovarymentioning
confidence: 99%
“…Moreover, like XIAP, expression of these IAPs is stimulated by gonadotrophins (Matsumoto et al 1999, Kumazawa et al 2004. A relationship between low Naip1 (Naip) mRNA expression levels in granulosa cells and reduced ovulated oocyte quality has been observed, indicating that NAIP may act indirectly to promote oocyte viability in the mouse ovary (Matsumoto et al 1999). Furthermore, immunoreactivity for survivin in oocytes has been observed at all follicle stages, and this IAP has been shown to play a direct role in meiotic maturation.…”
Section: Other Iaps In the Ovarymentioning
confidence: 99%
“…In fact, classification of NAIP as an IAP is based entirely on the conservation of the BIR domains, whereas the overall organization of the protein suggests membership in the NOD family of proteins with diverse physiological functions (24,25). The antiapoptotic function of full-length NAIP has been documented in a number of tissue culture and animal model systems (2,23,32,33), and the caspase-3-and -7-inhibiting activity of isolated BIR domains has been investigated in vitro (4). However, to date, no studies have examined the effect of the NOD and the LRR domain on the function of full-length NAIP.…”
Section: Fig 2 Interaction Of Caspase-9 With Xiap and Various Naip mentioning
confidence: 99%